A qualitative evaluation of youth awareness and perception towards depressive mental disorders through utilization of case-based scenarios - Bargayary, Harimu; Jain, Seema; Singh, Ganesh; Kumar, Sanjeev (International Journal Of Community Medicine And Public Health, 2025)
Background: Depression is a major contributor to global suicide rates and often coexists with substance abuse, complicating both treatment and outcomes. WHO reports that 3.8% of the global population suffers from depression, with the onset often occurring in adolescence or early adulthood. According to UNICEF, one in seven adolescents (aged 10-19 years) experiences a mental disorder, with anxiety and depression accounting for 40% of these cases, affecting approximately 166 million adolescents worldwide. In India, the National Mental Health Survey (2015-16) found that 5.3% of the population has experienced depressive disorders. 14% of Indian youth (aged 15-24) frequently feel depressed. Hence this study has been done to assess the awareness among youths regarding depressive mental disorders and their attitudes and perceptions regarding the conditions. Methods: This study was conducted in an urban area of Meerut district, Uttar Pradesh, India involving 475 youth participants, utilizing a case-scenario based questionnaire derived from the National Survey of Mental Health Literacy and Stigma Youth Boost Survey by Anthony F. Jorm and Nicola Reavley. Results: The study found that the rate of participants who could correctly identify the various depressive disorders based on the case-based scenarios presented to them were 236 (49.7%) for depression with suicidal ideation, 187 (39.4%) for depression alone, and 140 (29.5%) for depression with substance abuse. Conclusions: Suicidal ideation increases the likelihood of identifying depression, whereas depression alone is often underrecognized. Substance abuse further complicates the identification of underlying depression, resulting in the lowest recognition rates.